Find an expression which represents the sum of (4x + 1) and (-9x + 6) in simplest terms.

Question

Find an expression which represents the sum of (4x + 1) and (-9x + 6) in

simplest terms.

in progress 0
Delwyn 6 months 2021-08-10T01:46:50+00:00 1 Answers 8 views 0

Answers ( )

    0
    2021-08-10T01:47:50+00:00

    Answer:

    -5x+7

    Step-by-step explanation:

    Given: Two expressions are (4x+1),(-9x+6)

    To find: sum of the given expressions in simplest terms

    Solution:

    A variable is a term that takes various numerical values and a constant is a term that takes a fixed numerical value.

    Consider (4x+1)+(-9x+6)

    Here, solve (4x-9x),(1+6)

    4x-9x=(4-9)x=-5x\\1+6=7

    Therefore,

    (4x+1)+(-9x+6)=(4x-9x)+(1+6)=-5x+7

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )